KONTRIBUSI POLIMORFISME 1513 AC GEN P2X 7 TERHADAP KERENTANAN TUBERKULOSIS EKSTRAPULMONER - Susi Aulina, Irawan Yusuf, Suryani As’ad, Rizalinda Sjahril (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION TUBERCULOSIS TB IS A GLOBAL HEALTH PROBLEM A COMPLEX INTERACTION BETWEEN MYCOBACTERIUM TUBERCULOSIS GENOTYPE ENVIRONMENT AND HOST GOVERN THE DEVELOPMENT OF TB DISEASE BUT THE GENETIC VARIATION POLYMORPHISM IS LIKELY TO BE POLYGENIC IN NATURE THE MOST COMMON IDENTIFIED IS THE 1513 AC P2X7 GENE POLYMORPHISM